Wastewater management in Malaysia: a study of wastewater policies and implementation in Kajang district, Selangor - Azizi, Yasir Muda (2020)
Rapid and increasing urbanisation and economic growth has affected the land use and urban density changes in the district of Kajang, Selangor as in most parts of Malaysia. While development highlights the progress in spatial infrastructure planning and growth of the Malaysia economy, the challenges of urban infrastructure waste management such as wastewater planning and management are poorly researched and reported. This study investigates wastewater governance in Kajang district as a reflection of the policy implementation, short comings and management practices in Malaysia. It involves secondary and primary study of literatures on wastewater management in Malaysia. A questionnaire survey and face to face interviews were conducted to collect relevant data for evaluation and analysis. The survey covered the Kajang district of Selangor area, where sampled respondents included managers and workers that are involved in policy, management and operations in wastewater management. From the sample size of 100 questionnaire respondents, six interview sessions were conducted. The data were analysed using SPSS program for descriptive interpretations and thematic analysis. The results of the questionnaire survey and interviews showed that generally fairly efficient operation in wastewater management in Malaysia in general and in the Kajang District in particular however, some shortcomings in wastewater management due to lack of funds, manpower, equipments and skills. The analysis also found that there is also the matter of public awareness and the lack of understanding regarding wastewater generated and its implications in terms of pollution and management.